Sex differences in heart failure patients assessed by combined echocardiographic and cardiopulmonary exercise testing - Rozenbaum, Zach; Granot, Yoav; Sadeh, Ben; Havakuk, Ofer; Arnold, Joshua H.; Shimiaie, Jason; Ghermezi, Michael; Barak, Orly; Ben Gal, Yanai; Shacham, Yacov; Keren, Gad; Topilsky, Yan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: We aimed to test the differences in peak VO2 between males and females in patients diagnosed with heart failure (HF), using combined stress echocardiography (SE) and cardiopulmonary exercise testing (CPET). Methods: Patients who underwent CPET and SE for evaluation of dyspnea or exertional intolerance at our institution, between January 2013 and December 2017, were included and retrospectively assessed. Patients were divided into 3 groups: HF with preserved ejection fraction (HFpEF), HF with mildly reduced or reduced ejection fraction (HFmrEF/HFrEF), and patients without HF (control). These groups were further stratified by sex. Results: 178 patients underwent CPET-SE testing, of which 40% were females. Females diagnosed with HFpEF showed attenuated increases in end diastolic volume index (P= 0.040 for sex x time interaction), significantly elevated E/e' (p<0.001), significantly decreased left ventricle (LV) end diastolic volume:E/e ratio (P =0.040 for sex x time interaction), and lesser increases in A-VO2 difference (P=0.003 for sex x time interaction), comparing to males with HFpEF. Females diagnosed with HFmrEF/HFrEF showed diminished increases in end diastolic volume index (P= 0.050 for sex x time interaction), mostly after anaerobic threshold was met, comparing to males with HFmrEF/HFrEF. This resulted in reduced increases in peak stroke volume index (P= 0.010 for sex x time interaction) and cardiac output (P= 0.050 for sex x time interaction). Conclusions: Combined CPET-SE testing allows for individualized noninvasive evaluation of exercise physiology stratified by sex. Female patients with HF have lower exercise capacity compared to men with HF. For females diagnosed with HFpEF, this was due to poorer LV compliance and attenuated peripheral oxygen extraction, while for females diagnosed with HFmrEF/HFrEF, this was due to attenuated increase in peak stroke volume and cardiac output. As past studies have shown differences in clinical outcomes between females and males, this study provides an essential understanding of the differences in exercise physiology in HF patients, which may improve patient selection for targeted therapeutics.